Gambaran Kepuasan Petugas Rekam Medis Dalam Pengunaan Aplikasi Satu Sehat Di Rumah Sakit Daerah Idaman Banjarbaru - Eriseni Wati; Rina Gunarti; Isti Qomah; Ni Wayan Kurnia Widya Wati (HB PRESS, 2025)
Technological advances in the health sector have encouraged the implementation of health information systems, one of which is the satu sehat application. A preliminary study on satu sehat application at the Idaman Regional Hospital, Banjarbaru, faced obstacles such as limited data integration, information accuracy, interface display, and access speed. Therefore, a study was conducted on the satisfaction of medical record officers as application users. This study aims to determine the overview of medical record officer satisfaction with the satu sehat application using the End-User Computing Satisfaction (EUCS) method. This study uses a descriptive quantitative approach with data collection techniques through questionnaires, with the number of respondents in this study being 39 medical record officers. The results of this study indicate that the satisfaction of medical record officers based on the content dimension is 84.6% satisfied category, accuracy is 59.0% satisfied category, form is 94.9% satisfied category, ease of use is 69.2% dissatisfied category and timeliness is 84.6% satisfied category. Based on the results of the study, it can be concluded that the satu sehat application has provided benefits in terms of content, accuracy, appearance, and timeliness of information. However, the aspect of ease of use still needs to be improved. It is recommended that hospitals provide clear instructions, by socializing the one healthy application to medical record officers.